The case of Hojiblanca - Carneros E.M. (Present and future of the Mediterranean olive sector, 2013)
The Group Hojiblanca is a group of Spanish agricultural cooperatives, manly involved in olive oil production. It is currently the largest producer in the world, with an average production of 200,000 t of virgin olive oil and 67,000 t of table olives. It brings together the efforts of more than 50,000 families of olive producers through 96 oil mills and 22 olive processing plants. This paper aims at presenting the Group's history and future projects, that involve strengthening its role as reference olive oil operator in as many links as possible so that member farmers can increase profitability.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)